Values and Urban disorders and their implication to divorce a field study in Mosul city - Alsabaawi, Yousif Hamid; M. Fathi , Abdul Fattah (International Journal of Psychosocial Rehabilitation, 2025)
Divorce is one of the problems that afflicts all societies, as it is a problem that does not only concern the husband and wife, but its impact extends to children and the families of the spouses and the pattern of kinship relations between them, as well as its future repercussions on society through psychological and social disorders that will be inflicted upon the children after they are reached, and play many of the surrounding circumstances The family has a prominent role in the growing causes leading to divorce, and the process of reducing the severity of this problem requires the concerted efforts of many official and unofficial bodies and institutions through setting programs that qualify for marital life before starting them. Although the Iraqi city of Mosul is known for its adherence to inherited social customs and traditions, especially those that sanctify marital life in the manner in which divorce is considered a disgraceful social stigma attached to a divorced woman, her family, and her children, but a number of events and changes that Iraq has experienced (the US invasion of Iraq in 2003 The occupation of ISIS terrorist gangs in the city of Mosul in 2014, the blessed liberation operations from ISIS in 2017 And made the city of Mosul occupies advanced positions in terms of numbers of divorces at the level of all provinces of Iraq.